Integration of multiple theories for the simulation of laser interference lithography processes. (31st October 2017) - Lin, Te-Hsun; Yang, Yin-Kuang; Fu, Chien-Chung
Abstract: The periodic structure of laser interference lithography (LIL) fabrication is superior to other lithography technologies. In contrast to traditional lithography, LIL has the advantages of being a simple optical system with no mask requirements, low cost, high depth of focus, and large patterning area in a single exposure. Generally, a simulation pattern for the periodic structure is obtained through optical interference prior to its fabrication through LIL. However, the LIL process is complex and combines the fields of optical and polymer materials; thus, a single simulation theory cannot reflect the real situation. Therefore, this research integrates multiple theories, including those of optical interference, standing waves, and photoresist characteristics, to create a mathematical model for the LIL process. The mathematical model can accurately estimate the exposure time and reduce the LIL process duration through trial and error.